2014
DOI: 10.1111/ijcp.12407
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of lipid abnormalities and attainment of normal lipid levels among patients with dyslipidaemia: a pooled analysis of observational studies from five Asian countries

Abstract: Aims: Guidelines emphasise the importance of low-density lipoprotein cholesterol (LDL-C) goals for cardiovascular risk reduction. Given the importance of association between high-density lipoprotein (HDL-C) and triglycerides (TG) normal levels and cardiovascular risk, there is an additional need to further evaluate diverse dyslipidaemic populations. Methods: A retrospective longitudinal observational study of patients aged ≥ 35 years on lipid-modifying therapy (LMT) for ≥ 12 months was conducted from patient r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
4
1
Order By: Relevance
“…The prevalence of raised LDL-c in our study was 21%. This rate is lower than the studies reported by Iloh et al (2012) and Unniachan et al (2014). The prevalence rate in these two studies was 23.8% and 86.2%, respectively.…”
Section: Discussioncontrasting
confidence: 67%
“…The prevalence of raised LDL-c in our study was 21%. This rate is lower than the studies reported by Iloh et al (2012) and Unniachan et al (2014). The prevalence rate in these two studies was 23.8% and 86.2%, respectively.…”
Section: Discussioncontrasting
confidence: 67%
“…Numerous papers have reported the data on lipid profile and dyslipidemia prevalence in different countries and regions worldwide, indicating the real need and importance of having data on the national characteristics of these disorders, including socioeconomic, behavioral, metabolic, and hereditary peculiarities [ 13 , 14 , 15 , 16 , 17 , 18 ]. However, in most studies, only trends of means of TC, HDL-C, and non-HDL-C have been assessed, and the analysis did not include other lipids of interest to researchers and clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…There are accumulating data showing that the burden of ASCVD and dyslipidemia is increasing across developing countries: while age-specific ASCVD in many high-income countries is declining, the prevalence of plasma lipid disorders in the Asia-Pacific region is rising [14,17]; similar data were reported for Mexico [19]. In a recent review, Carrillo-Larco et al demonstrated that the most common type of dyslipidemia in Latin America and the Caribbean region since 2005 is low HDL-C level (48%), followed by elevated TG (21%) and high LDL-C (20%) [21].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in other countries have shown that the poor LDL-C control rate for high-risk patients treated in general practice is a global problem [31][32][33]. In South Africa, the control rate for very high-risk patients was reported to be only 26.5%.…”
Section: Treatment Aims and Low-density Lipoprotein Cholesterol (Ldl-mentioning
confidence: 99%